Universal and Seamless Control of Distributed Resources-Energy Storage for all Operational Scenarios of Microgrids - Meghdad Fazeli (IEEE Transactions on Energy Conversion, 2017)
This paper proposes one control paradigm that can operate in both grid-connected and islanded modes, hence, does not need any sort of islanding detection method. The proposed method automatically and seamlessly rides-through a fault on the grid side, and controls the microgrid’s voltage and frequency during islanded operation. During islanded operation it utilises the combination of distributed generation-energy storage similar to the prime-mover of a synchronous generator to control the frequency. A comprehensive active and reactive power control is proposed that minimises the usage of a local fossil-fuelled auxiliary generator. The method is based on expanding the so called non-detection zone to all operational scenarios including islanded mode, hence, having small, “undetectable” voltage and frequency deviation. As soon as the grid is reconnected the distributed generator is automatically and seamlessly synchronised with the grid. This is achieved through keeping PLL as part of the operation in islanded mode without altering its phase angle. The proposed method is validated using PSCAD/ EMTDC simulation.